"Hay que tener suerte": Gender-based Violence Service Provision in Quito, Ecuador - Chiara Sabina; Diego Pérez Figueroa (Harvard FXB Center for Health and Human Rights, 2019)
This study utilized the United Nations' Essential Services Package for Women and Girls Subject to Violence, a technical guidebook on quality services in line with human rights declarations, to examine the characteristics of availability, accessibility, adaptability, and appropriateness from the viewpoint of 21 victim service users in Quito, Ecuador. Availability was evidenced by warm service providers willing to aid victims but was hindered by a failure to make available all desired services (such as those related to economic empowerment). Accessibility was aided by service locations that were easily accessible and by referrals, but a lack of information and conflicting schedules thwarted users' help-seeking efforts. Participants shared experiences of services adapted to their specific needs and experiences of violence, but additional services were needed to fully attend to their particular circumstances. Participants shared how service providers empowered them by listening to their experiences and helping them move forward in their lives. Nonetheless, participants shared experiences of victim-blaming and other harmful attitudes from providers. Overall, there was a great amount of variability in participants' service experiences. Areas for consideration include economic empowerment, expansion of services to men and children, increased access to information, and trauma-informed training of staff in order to better respond to gender-based violence.